Conflict and Representation: Dahrendorf’s theory in the context of contemporary populism - Bola, José (Cadernos IS-UP, 2025)
Based on an extensive literature review, this article examines Ralf Dahrendorf’s theory of social conflict in the context of contemporary populism. It aims to explore Dahrendorf’s view on the inherent nature of conflict in modern societies and how this phenomenon can help to understand populist dynamics, particularly regarding the relationship between elites and subordinate groups. The (contemporary) city, a stage for multiple confrontations and tensions that divide society into hierarchical groups, is not merely a physical place but a field of social and political representation where rights and access to the ‘commons’ — understood as shared spaces and resources — are contested and reconfigured. Based on the argument that populist leaders exacerbate latent social conflicts by fostering a divide between the “people” and the “elites”, creating an antagonism that rallies society around a polarising narrative, this article analyses not only examples of contemporary populism, but also the manipulation of social and political representations driven by democratic instability.